2018
DOI: 10.1523/eneuro.0330-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Drug Effects on Probability Weighting during Risky Decision Making

Abstract: Dopamine has been associated with risky decision-making, as well as with pathological gambling, a behavioral addiction characterized by excessive risk-taking behavior. However, the specific mechanisms through which dopamine might act to foster risk-taking and pathological gambling remain elusive. Here we test the hypothesis that this might be achieved, in part, via modulation of subjective probability weighting during decision making. Human healthy controls (n = 21) and pathological gamblers (n = 16) played a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…Primate studies found that sustained dopamine neuron activity signaled expected uncertainty ( Fiorillo et al, 2003 ; Schultz, 2010 ; Schultz et al, 2008 ). This was further supported by human pharmacological studies ( Burke et al, 2018 ; Ojala et al, 2018 ) as well as fMRI research showing possible involvement of dopamine in risk taking and of dopaminoceptive regions, such as the caudate, anterior insula, ACC and the medial PFC in uncertainty coding (e.g. Dreher et al, 2006 ; Preuschoff et al, 2008 ; Tobler et al, 2009 ) and social advice predictions under uncertainty ( Henco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 75%
“…Primate studies found that sustained dopamine neuron activity signaled expected uncertainty ( Fiorillo et al, 2003 ; Schultz, 2010 ; Schultz et al, 2008 ). This was further supported by human pharmacological studies ( Burke et al, 2018 ; Ojala et al, 2018 ) as well as fMRI research showing possible involvement of dopamine in risk taking and of dopaminoceptive regions, such as the caudate, anterior insula, ACC and the medial PFC in uncertainty coding (e.g. Dreher et al, 2006 ; Preuschoff et al, 2008 ; Tobler et al, 2009 ) and social advice predictions under uncertainty ( Henco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 75%
“…In ADHD patients, MPH enhanced the hypoactive vmPFC on placebo comparable to the observed levels of healthy controls 2 . Dopaminergic medications increase risk-taking by changing the subjective weighting of the reward probabilities 34 or by increasing the baseline gambling tendency 35 . In this study, it is very likely to have similar effects where MPH via D1 and α 2 -norepinephrine receptors enhanced the vmPFC activity (one of brain's core valuation system 36 ) and altered the subjective value of the choices.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that we had predicted an increasing rather than a reducing effect of sulpiride on the average number of clicks based on the assumption that the relatively low dose of 200 mg primarily blocks presynaptic autoreceptors, resulting in a reduction of postsynaptic DA activity (Kuroki et al, 1999;Mereu et al, 1983), thus increasing approach motivation. Studies investigating sulpiride's effects on reward processing and its neurophysiological correlates often use higher dosages of up to 800 mg resulting in predominantly inhibiting effects (Diederen et al, 2017;Ojala et al, 2018;Weber et al, 2016;Eisenegger et al, 2014). However, it might be possible that administering a single dose of sulpiride evokes inhibiting effects even when used in smaller dosages.…”
Section: Validity Of the Modified Version Of The Eefrtmentioning
confidence: 99%
“…While, for example, Kahnt, Weber, Haker, Robbins, & Tobler (2015) failed to find behavioral changes after the intake of 400 mg amisulpiride within an outcome prediction task, Diederen et al (2017) found that participants' ability to predict future rewards was reduced after intake of 600 mg sulpiride. Ojala et al (2018) reported that the intake of 400 mg of sulpiride reduced healthy participants overweighting of low probabilities within a decision-making task, resulting in less risky choices. Weber et al (2016) found that 400 mg of amisulpiride reduced participants' motivation to choose immediate rewards in a delay-discounting task.…”
mentioning
confidence: 99%